Facile preparation of a three-coordinate copper(I) complex: Steric hindrance, supramolecular structure, optical property and TD-DFT study. (2nd August 2016) - Zhao, Yi; Chai, Wen-Xiang; Song, Li; Zhang, Yi-Cheng; Shi, Hong-Sheng; Tao, Xiao-Dong; Shu, Kang-Ying
GRAPHICAL ABSTRACT: ABSTRACT: The solution reaction of Cu(CH3 CN)4 (PF6 ) with a NN ligand 2-(2′-quinolyl)benzimidazole and a sterically bulky P ligand tris(2-methylphenyl)phosphine facilely yielded the three-coordinate copper(I) complex [Cu(2-QBI)(o-Tol3 P)](PF6 ) (1 ). The complex has been characterized by single-crystal X-ray diffraction, Fourier Transform infrared spectroscopy and elemental analysis, UV–Vis (ultraviolet–visible) and photoluminescent spectroscopy studies. Time-dependent density functional theory has been used for calculating the electronic origin of the low-lying excited states, which were unexpectedly assigned mainly as a ligand-to-ligand or an intra-ligand charge transfer state instead of the metal-to-ligand charge transfer transition. Interestingly, 1 exhibits a concentration-dependent absorption in solution. This absorption behavior is interpreted as some excimer's formation based on the study of supramolecular structure, spectroscopy and calculations.